2009
DOI: 10.1007/s12028-009-9283-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of ECG Abnormalities After Intracerebral Hemorrhage

Abstract: In ICH patients ECG abnormalities are common. QTc prolongation seems associated with insular cortex involvement, with the presence of intraventricular blood, and with hydrocephalus. A larger cohort of continuously monitored ICH patients is necessary to investigate whether these ECG abnormalities are associated with poor outcome or death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 32 publications
0
34
0
2
Order By: Relevance
“…ANP release is triggered by volume challenge of the cardiac atrium [20]. Alterations of ANP levels in hemorrhagic stroke patients seem to be multifactorial: cardiac abnormalities are common in patients with (severe) SAH and ICH [21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…ANP release is triggered by volume challenge of the cardiac atrium [20]. Alterations of ANP levels in hemorrhagic stroke patients seem to be multifactorial: cardiac abnormalities are common in patients with (severe) SAH and ICH [21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…In patients with primary nontraumatic intracerebral hemorrhage (other than subarachnoid), QTc prolongation was the most frequently encountered abnormality (36%) followed by ST-T changes (23%) and T wave inversion (16%) (324). QTc prolongation was associated with insular involvement, but no other ECG attribute was associated with lesion location.…”
Section: Insular Stroke and Its Effect On Cardiac Repolarization And mentioning
confidence: 95%
“…10 It is well known that electrocardiographic abnormalities are common in patients with ischemic stroke, hemorrhagic stroke, and SAH. 8,11,12 Abnormalities on electrocardiogram that might lead to cardiac arrest such as QT prolongation are common in patients with stroke. 8,11 A recent meta-analysis in patients with SAH showed that markers of cardiac damage and dysfunction are associated with poor outcome and mortality.…”
Section: Vergouwen Et Al Complications After Clipped and Coiled Aneurmentioning
confidence: 99%
“…8,11,12 Abnormalities on electrocardiogram that might lead to cardiac arrest such as QT prolongation are common in patients with stroke. 8,11 A recent meta-analysis in patients with SAH showed that markers of cardiac damage and dysfunction are associated with poor outcome and mortality. 13 Damage to the insular cortex in patients with stroke has been associated with electrocardiographic abnormalities.…”
Section: Vergouwen Et Al Complications After Clipped and Coiled Aneurmentioning
confidence: 99%